The Influence of Healthcare Service Quality on Patient Satisfaction at Balung Health Center - Yetik Rukmana Wijayanti; Roro Aditya Novi Wardhani; Hanif Hadinata Utama (PROMOTOR, 2026)
Community Health Centers (Puskesmas) serve as primary healthcare facilities that play a vital role in improving public health through promotive and preventive services. However, the quality of services in various regions, including Jember Regency, continues to face several challenges. Data indicate a decline in the Community Satisfaction Index (IKM) from 81% in 2023 to 79% in 2024, reflecting a decrease in patient satisfaction. Balung Health Center has become a focal point due to patient complaints regarding the lack of friendliness among healthcare workers, limited medical facilities, and a shortage of doctors. This study aims to analyze the effect of service quality on patient satisfaction using a quantitative approach based on the SERVQUAL model. Findings indicate that service quality significantly affects patient satisfaction, with reliability being the most dominant factor.